Implementation of Smart Airport Technologies at Selected Airports: Qualitative Assessment - Matus MATERNA; Alena NOVAK SEDLACKOVA; Illkan COSKUN (Communications of International Proceedings, 2021)
The aim of the paper is to analyse implementation of Smart Airport technologies at selected airports. Paper offers introduction to the issue via literature overview. Paper also proposes qualitative analysis of Smart Airport technologies implementation at 8 selected airports (Istanbul, Singapore, Hamad, London, Amsterdam, Tokyo, Soul and Brussels) in order to examine the extent to which they meet the criteria for Smart Airports. Results suggest that all examined airports have implemented most of the digital transformation tools and achieved the status of the “Smart Airport.”
Keywords: Smart airports; qualitative assessment; industry 4.0